ChemInform Abstract: Cu(I)‐Catalyzed Enantioselective Friedel—Crafts Alkylation of Indoles with 2‐Aryl‐N‐sulfonylaziridines as Alkylating Agents. Issue 47 (3rd November 2016) - Ge, Chen; Liu, Ren‐Rong; Gao, Jian‐Rong; Jia, Yi‐Xia
Abstract: The scalable procedure provides tryptamine derivatives in high yields and with high enantioselectivities.